Development of a method for obtaining a CdS/CdTe/Cu/Au module on a flexible substrate designed for backup supplying systems prevention of emergency situations - Deyneko , Natalia; Yeremenko , Sergey; Kamyshentsev , Gennady; Kryvulkin , Igor; Matiushenko , Mykola; Myroshnyk , Oleg; Pruskyi , Andrei; Soshinsky , Alexander; Strelets , Victor; Shevchenko , Roman (Eastern-European Journal of Enterprise Technologies, 2021)
The study of methods for obtaining base layers of cadmium telluride for the creation of efficient solar cells on a flexible substrate, intended for backup power supply of security systems and facility control. Considering that the polyamide film is stable up to a temperature of 450 °С, the formation of the base layers of solar cells based on cadmium telluride on flexible polyamide substrates was carried out by the method of DC magnetron sputtering. Using the chosen method, experimental samples of micromodules on a flexible substrate with series-connected solar cells based on CdS/CdTe/Cu/Au were obtained. To understand the effect of the failure of one or more solar cells on the efficiency of the entire micromodule during operation, an analysis of the initial parameters and light diode characteristics of individual solar cells of micromodules was carried out. The design of the micromodules, in which the solar cells were connected in series, made it possible to separately measure their output parameters. It was found that the creation of a Cu/Au rear tunnel contact made it possible to obtain high values of the output parameters for individual solar cells, but the micromodule contains a limitation by a shunted solar cell. However, the greatest role in reducing the efficiency of the entire micromodule is played by ineffective absorption of radiation when passing through the polyamide film, which led to a decrease in the efficiency of the entire micromodule, in which there is a shunted element, to 3.9 %. The maximum efficiency of the obtained samples of micromodules was 5.3 %